Stitching Identity: The Role of Handicrafts in Cultural Protection by Ikatan Wanita BRI (IWABRI) in Blora - Nur Hidayah (Lembaga Pengembangan Kinerja Dosen, 2024)
This community service project aims to highlight the significant role of handicrafts in preserving cultural identity, particularly in the context of Blora. Ikatan Wanita BRI (IWABRI) has been actively involved in promoting traditional handicrafts as a means of empowering women and revitalizing local communities. By providing training and resources, IWABRI help artisans to create unique and sustainable products that reflect the rich cultural heritage of Blora. The methodology employed in this community service initiative was Participatory Action Research (PAR), a strategic framework designed to foster learning and address community needs concurrently. This approach encompassed five stages: understanding, planning, acting, changing, and knowing. A total of 21 individuals participated in the program. The initiative successfully enabled participants to conceptualize and produce handicraft designs from inception to completion. However, the quality of the final products varied due to individual skill disparities.